Pharmacokinetics and protein binding interactions of dapsone and pyrimethamine - Ahmad, RA; Rogers, HJ (British journal of clinical pharmacology, 1980)
1 Seven normal volunteers received oral doses of 100 mg dapsone (DDS), 25 mg pyrimethamine (PYR) singly or in combination in random order. 2 Plasma and salivary DDS and plasma monoacetyldapone (MADDS) and PYR were estimated simultaneously by a hitherto unpublished quantitative absorption thin layer chromatographic method. This assay was shown to be satisfactory for pharmacokinetic studies. 3 The half‐life of DDS was unaltered by PYR but the apparent volume of distribution was significantly increased from a mean of 1.53 1 kg‐1 to 1.93 1 kg‐1 and the peak DDS plasma levels measured fell by 17%. 4 The pharmacokinetic parameters of PYR were unchanged by DDS. 5 The half‐life of MADDS was unchanged by PYR and was not affected by the acetylator status of the subject. 6 Salivary DDS excretion reflects the free plasma DDS concentration. Administration of PYR with DDS significantly alters the mean saliva/plasma DDS ratio from 0.265 to 0.358 suggesting an increase in free DDS with PYR therapy. 7 In vitro studies of plasma protein DDS binding indicate that DDS binds to a single class of binding sites on human plasma protein and PYR competitively displaces DDS from these sites. 8 The usefulness of salivary drug measurements in detecting increases of free drug in plasma in man is demonstrated.